Assessment of Conservation Voltage Reduction Effects in Networks with Distributed Generators - Quijano, D. A. [UNESP] (2015)
Conservation Voltage Reduction (CVR) has been an efficient way to achieve power demand reduction and, consequently, a relief in distribution networks. In this work is presented an assessment of the distributed generation (DG) impacts on the efficiency achieved with the CVR. The DG is considered as a controllable source of active and reactive power through an approach based on an integrated Volt-Var control (IVVC). It is expected, that centralized control methodologies will be increasingly present in distribution networks, in a scenario with the so-called smart grids. The analysis is made for the network operation phase through a simulation-based method. Tests were performed on a 95 bus test system using the multiobjective algorithm NSGA-II as optimization tool. Conclusions are made by comparing scenarios of DG with and without reactive power control capability.